SERUM BRAIN DERIVED NEUROTROPHIC FACTOR AS BIOMARKER FOR EPILEPSY DIAGNOSIS IN EGYPTIAN CHILDREN WITH EPILEPSY; RELATIONSHIP TO DISEASE SEVERITY AND COGNITIVE FUNCTION. - El-alameey, Inas R; Ahmed, Hanaa H (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: This study was designed to estimate serum brain-derived neurotrophic factor (BDNF) concentration in a group of Egyptian children with epilepsy to clarify its utility as a biomarker for epilepsy diagnosis and to evaluate its relationship with their cognitive function and disease severity. Methods: Intelligence was assessed using Arabic version of the WISC-R test. Serum concentration of BDNF was assessed using enzyme-linked immunosorbent assay in 40 children with epilepsy and 40 apparently healthy children of matched age and sex controls. Results: Of total 40 epileptic patients aged 6â€“12 years, the mean age was 8.32 Â± 0.7 years and male to female ratio was 1.5:1. The mean serum BDNF concentration and cognitive IQ scores were statistically significantly reduced in the studied patient’s group versus to controls (p<0.001). There were highly significant differences in serum BDNF concentration as regards epileptic severity. Serum concentration of BDNF showed significantly positive correlation with cognitive, verbal, performance, and totals IQ scores and negative correlation with the age at the onset of seizures, and duration of therapy. The linear regression analysis showed a statistically significant association between age at the onset of seizures, duration of therapy, cognitive function, and serum BDNF concentrations among the studied patients. Conclusions: Concentration of BDNF in serum is involved in the mechanism of epileptogenesis in children with epilepsy. It should be used as a helpful marker for epilepsy diagnosis and detection of severity.